AN ANTIDIABETIC ACTIVITIES OF CINNAMON EXTRACT IN MICE BY THE METHOD OF INDUCTION OF ALLOXANE - M. Perdiansyah Mulia Harahap; Subeki Subeki (Jurnal Pengembangan Agroindustri Terapan, 2022)
Diabetes mellitus or sugar disease is a metabolic disease with hyperglycemia characteristics that occur due to abnormalities in insulin secretion, insulin work, or both are currently experienced by many Indonesian people. Based on Basic Health Research in Indonesia, diabetics have increased significantly over the past five years.  In 2013, the prevalence rate of diabetes in adults in Indonesia itself, based on the latest data from the 2018 Basic Health Research, in general the prevalence rate of diabetes in adults reached 6.9% and in 2018 the figure increased to 8.5%. This study aims to analyze the antidiabetic activity of cinnamon extract in alloxane-induced mice and the content of bioactive compounds that have antidiabetic activity. Cinnamon extract was carried out by maceration using 96% methanol compounds for 4 weeks followed by ethyl acetate extraction 4 times. Purification was performed using chromatographic columns with solvents CHCl3, 3% MeOH-CHCl3, 20% MeOH-CHCl3, MeOH. Each purification fraction was tested In Vivo on mice. The test results showed that cinnamon powder extract at a fraction of MeOH-CHCl3 3% can significantly reduce blood glucose levels compared to the control treatment of 113: 392  (mg/dL).